2013
DOI: 10.3389/fneur.2013.00042
|View full text |Cite|
|
Sign up to set email alerts
|

Dense Array EEG Source Estimation in Neocortical Epilepsy

Abstract: Rationale: Dense array EEG (dEEG) evenly covers the whole head surface with over 100 channels contributing to more accurate electrical source imaging due to the higher spatial and temporal resolution. Several studies have shown the clinical utility of dEEG in presurgical clinical evaluation of epilepsy. However validation studies measuring the accuracy of dEEG source imaging are still needed. This can be achieved through simultaneously recording both scalp dEEG with intracranial electrodes (icEEG), which is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…It is well established that the accuracy of EEG study can be improved by increasing spatial sampling with higher number of EEG electrodes (Lantz et al, 2003;Yamazaki et al, 2013). In support of this, we observed no 'ceiling effect' with respect to the electrode count (Figs.…”
Section: Effects Of Increasing Electrode Numberssupporting
confidence: 77%
“…It is well established that the accuracy of EEG study can be improved by increasing spatial sampling with higher number of EEG electrodes (Lantz et al, 2003;Yamazaki et al, 2013). In support of this, we observed no 'ceiling effect' with respect to the electrode count (Figs.…”
Section: Effects Of Increasing Electrode Numberssupporting
confidence: 77%
“…Multiple studies have demonstrated the utility of electrical source imaging (ESI) of high density EEG recordings for improved localization of epileptic foci in surgical candidates compared to visual interpretation of the conventional scalp EEG (Lantz et al, 2003; Holmes et al, 2008, 2010; Yamazaki et al, 2013; Storti et al, 2013; Mégevand et al, 2014; Michel et al., 2004a,b; Brodbeck et al, 2010; Zumsteg et al, 2005; Lantz et al, 2001; Brodbeck et al, 2009). A large prospective study in 151 pediatric and adult epilepsy surgery patients found that ESI using 126–256 channels and individual brain MRIs as the head model yielded a sensitivity of 84% and a specificity of 88% in identifying the seizure onset zone, which was significantly better than that obtained using low-density EEG recordings, structural MRI, PET exam, or ictal SPECT exams (Brodbeck et al, 2011).…”
mentioning
confidence: 99%
“…In their chapter in this volume, Yamazaki et al (7) extend this work to cases of neocortical epilepsy by demonstrating that dEEG, by covering the whole head with sufficient sensor density, can reliably localize epileptiform discharges when compared to invasive studies.…”
mentioning
confidence: 98%
“…Yamazaki et al (7) have pioneered the ability to simultaneously record 256 channel dense EEG (dEEG) and invasive subdural EEG recordings in temporal lobe epilepsy, thus helping to establish the validity of dEEG recordings. In their chapter in this volume, Yamazaki et al (7) extend this work to cases of neocortical epilepsy by demonstrating that dEEG, by covering the whole head with sufficient sensor density, can reliably localize epileptiform discharges when compared to invasive studies.…”
mentioning
confidence: 99%